2022
DOI: 10.1155/2022/1690458
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Some Lifetime Parameters of Flexible Reduced Logarithmic‐Inverse Lomax Distribution under Progressive Type‐II Censored Data

Abstract: In this study, the estimation of parameters of a three-parameter flexible reduced logarithmic-inverse Lomax (FRL-IL) distribution based on progressive type-II right censored sample is studied. These methods include maximum likelihood estimations (MLEs) and Bayesian estimators. Approximate confidence intervals (ACIs) for the reliability and hazard functions are estimated based on the asymptotic distribution of maximum likelihood estimates (MLEs). In addition, two bootstrap CIs are also proposed. Bayesian estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Balakrishnan [10] investigated the characteristics under progressively censored samples and reported that a collection of several advances in the inferential procedures depend on types-I and -II censored samples, Almetwally et al [11] studied the MLE and BE method to determine the parameters of the EGE distribution under progressive censoring. Buzaridah et al [12] and Khalifa et al [13] studied estimations of the distribution parameters under Prog-II censored data and Chen and Gui [14] presented statistical inference of the joint Prog-II censored generalized inverted exponential distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Balakrishnan [10] investigated the characteristics under progressively censored samples and reported that a collection of several advances in the inferential procedures depend on types-I and -II censored samples, Almetwally et al [11] studied the MLE and BE method to determine the parameters of the EGE distribution under progressive censoring. Buzaridah et al [12] and Khalifa et al [13] studied estimations of the distribution parameters under Prog-II censored data and Chen and Gui [14] presented statistical inference of the joint Prog-II censored generalized inverted exponential distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using real datasets provided by Dumonceaux and Antle [12], the 20 flood levels represent a real dataset of Susquehanna River's maximum flood levels at Harrisburg, Pennsylvania, between 1890 and 1969. The data are as follows:…”
Section: Flood-level Datamentioning
confidence: 99%
“…However, there are difficulties in recognizing the distribution. So far, the well-known methods for estimating the parameters of distribution data are the Method of Moments, the Method of Maximum Likelihood Estimation, the Method of Probability Weighted Moment, and the Richardson Method [9][10][11]. Those methods have some weaknesses [12], including: (1) an iterative procedure for maximum likelihood estimation is based only on a complete sample of various population parameters; (2) the solution is only based on a linear system; (3) the method cannot find the precise parameter if the system has more than one peak (4), the method cannot find the parameter if the distribution members are infinite, (5) the solution requires complex mathematical solving skills, such as integral approach [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…, S r ) are predetermined and fixed. A useful description and good summary of progressive censoring (PC) can be found in [23][24][25][26][27][28][29][30][31][32][33][34]. It should be noted that, when S 1 = S 2 = .…”
Section: Introductionmentioning
confidence: 99%